Mapping Hate Speech Relationships Indonesia's Religion and State in Social Media - Sazali, Hasan; SM, Umar Abdur Rahim; Marta, Rustono Farady; Gatcho, Al Ryanne Gabonada (Fakultas Dakwah dan Komunikasi UIN Sunan Gunung Djati Bandung, 2022)
Social media has also become a public sphere for people to express all expressions, opinions, ideas, and feelings, including conveying hate speech. In Indonesia, there are many forms of hate speech, one of which leads to issues of racism and religious and state sentiment. This study will identify the problem of hate speech related to religion and the state on social media. This study is a descriptive qualitative study by taking data from Social Media Analysts using a query for hate speech words that have a relationship between religion and the state that are popular in Indonesia, namely the terms Kadrun and Cebong. The first result shows that around 52,290 thousand mentions containing hate speech using the word kadrun and 25,290 thousand statements using the word cebong as a form of negative response to issues that contribute to the background, the case of contradiction between religion and the state. The second religious issue has become a trending issue in the digital era and is most readily associated with political matters in spreading hate speech. Three Twitter media are one of the most frequently used social media platforms compared to other media in spreading hate speech by Indonesia's digital community. This research implies the development of perspectives from both labels to bring down the opposition's reputation during certain political events.